Perceptions on river conservation issues in Cameron Highlands - Abdul Aziz, Nurazriena (2019)
The rapid and intense growth of tourism, urban development and agriculture in Cameron Highlands contributed to river pollutions in that area. Apart from environmental and economic factors, the social aspect is also essential to be considered in the decision-making process of conservation. Study of perceptions on river conservation issues in Cameron Highlands provides information of public knowledge level towards river pollution and level of concerns towards river conservation measures in Cameron Highlands. This study used Spearman correlation analysis as a method to determine the association between perceptions on river conservation issues in Cameron Highlands with specific socio-demographic. Data were obtained using a closed-ended questionnaire through an interview. The respondents were asked on their strength of agreement regarding on river pollution issue and conservation measures of the river in Cameron Highlands. About 123 respondents were involved in this study. This study found that the factor of gender, age, and educational level is significant to perceptions of river conservation issues. The approach in determining perception on river conservation measures in Cameron Highlands helps provide some guidelines and obtain extra information for decision-making process especially related to river pollution issue and river conservation in Cameron Highlands.